Detecção do Foot-and-mouth disease virus em líquido esofágico faríngeo (LEF) bovino por RT-qPCR análise comparativa do desempenho de reagentes de inativação viral - Luciana Rabello Ferreira (2020)
FMD is caused by foot-and-mouth disease virus (FMDV), an RNA virus of the family Picornaviridae, which infects biungulate animals, ruminants and domestic and wild swine throughout the world. Seven viral serotypes are described - A, O, C (already reported in Brazil), Asia 1, SAT 1, SAT 2 and SAT 3. Clinical signs of infection include vesicle formation and epithelial erosions on tongue, hard and soft palate and the coronary band of the hull, which are not clinically distinguishable from other vesicular diseases. FMD is one of the main constraints to international trade in animal products, because it is highly contagious and presents a broad host spectrum. Rapid and accurate diagnosis and epidemiological surveillance are of vital importance to the national economy. In the Federal Agricultural Defense Laboratory of Minas Gerais State (LFDA-MG), a national reference center for molecular diagnosis of the FMD, the RT-qPCR is carried out to detect conserved regions from the FMDV genome. The guarantee of biosafety is an essential factor for effective work in Agricultural Defense, therefore every suspected sample of vesicular disease is considered positive for Foot-and-Mouth Disease from moment it arrives from the field until the viral inactivation process. The oesophageal–pharyngeal sample (OP) is the sample designated by the World Organization for Animal Health (OIE) for the diagnosis of FMDV in cattle.The present work compared the performance of the MagMaxTM CORE Lysis Solution and TRIzol® (regularly used) for viral inactivation using bovine OP samples experimentally contaminated with FMDV serotype O [RS BR / 80]. The performance of the molecular diagnostic method for FMD from viral inactivation to RT-qPCR, followed the criteria of the Performance Verification Guide of the Laboratory Support Coordination (CGAL) of the Ministry of Agriculture, Livestock and Food Supply (MAPA). The effectiveness of viral inactivation by the MagMaxTM CORE Lysis Solution was proven by viral isolation tests using BHK21 cells. Three blind passages indicated the absence of infectious viral particles in the dilutions corresponding to 100.01 to 10-1.99 TCID50/ 50 µL. The performance of the RT-PCR under the tested inactivation conditions established a Detection Limit of 101.7 TCID50/50µL for both inactivators used; efficiency of 98.0% and 94,4%, repeatability variances of 7,33% and 10,76%, intra-laboratory reproducibility of 9,99% and 16,49%, method measurement error of 17,32% e 27,26% and expanded uncertainty of 0,64 e 0,94 Ct for MagMaxTM CORE Lysis Solution and TRIzol®, respectively. The averages estimated by the multiple regression model established for the tested methods of viral inactivation showed superiority of all tested parameters for samples inactivated by MagMaxTM CORE Lysis Solution, even when the amplification kit was varied. In addition, this inactivating solution showed a savings of 35.3% in the final value of each LEF sample tested.